PROFILE OF STATE PREHOSPITAL MOBILE EMERGENCY CARE SERVICE - Jaciana Medeiros da Costa Dias; Maria Solange Moreira de Lima; Rodrigo Assis Neves Dantas; Isabel Karolyne Fernandes Costa; José Eugênio Lopes Leite; Daniele Vieira Dantas (Universidade Federal do Paraná, 2016)
The aim of the present study was to identify the epidemiological and health profile of care provided by the Emergency Mobile Care Service of the state of Rio Grande do Norte, Brazil, between January and April 2014. This was a descriptive, exploratory and quantitative study based on retrospective data. Data were gathered between July and September 2014 using a pre-determined instrument. We analyzed 3,186 incidents, of which 1,473 were clinical, 1,454 traumatic, 79 obstetric, and 180 psychiatric. Furthermore, 2,012 (63.2%) consisted of male victims and individuals between 25 and 34 years old represented the most common age group. The day period totaled 58.3% of incidents. Basic Support Units carried out 90.4% of care. The results showed that the characterization of this service is relevant to substantiate the creation of health policies and actions compatible with the identified needs.